Radio Systems Engineering A Tutorial Approach - De Los Santos, Héctor J (Springer, 2015)
This book is intended for readers who already have knowledge of devices and circuits for radio-frequency (RF) and microwave communication and are ready to study the systems engineering-level aspects of modern radio communications systems. The authors provide a general overview of radio systems with their components, focusing on the analog parts of the system and their non-idealities. Based on the physical functionality of the various building blocks of a modern radio system, block parameters are derived, which allows the examination of their influence on the overall system performance.